Validitas Dan Reliabilitas Skala Karakter Sopan Santun Pada Siswa SMA Kelas X Di Nganjuk - Ula Azizah; Andrianie, Santy; Arofah, Laelatul; Azizah, Ula (Efektor, 2021)
Manners character of courtesy is very necessary for students in each individual. Students who have a strong character of manners will not lead to moral decline and will become a hallmark of students, namely students who have high polite character.To be able to find out how big the students’ character is, an instrument is needed in the form of a polite character scale. With this scale, it is hoped that students will map their polite and reliable character. This study aims to determine the validity and reliability of the politeness character scale. The development of this polite character scale uses six steps of compiling instruments from Riduwan which are modified according to needs. The results of the analysis of the validity and reliability test using product moment correlation and Cronbach's alpha obtained 29 valid statement items with an r alpha reliability of 0.928 meaning they are in the high category,which means that the polite character scale can be used by BK teachers to map the polite character of high school students X.